Psychotherapists’ readiness to treat PTSD: the influence of refugees’ country of origin - Pia Maria Schwegler; Katharina Gossmann; Theresa Neumann; Anne Moser; Theresa Speth; Rita Rosner (European Journal of Psychotraumatology)
Background: Previous research suggests that psychotherapists’ readiness to treat traumatized patients varies according to patient and therapist characteristics, including the patient's refugee background.Objective: This study aims to examine the relationship between psychotherapists’ readiness to treat patients with symptoms of post-traumatic stress disorder and various patient and therapist characteristics, including refugee background and country of origin.Method: In our vignette study with a nationwide online survey in Germany (N = 871), we assessed the readiness of licensed psychotherapists (LPTs) and therapists in training (PiTs) to treat patients with PTSD. Vignettes described patients with PTSD who differed in gender, refugee background, and country of origin (Syria vs. Ukraine). Participants rated treatment readiness and expected treatment success based on the vignette they received.Results: Treatment readiness and expected success were significantly lower for refugee patients. There was no difference in treatment readiness between refugees from Syria and Ukraine, but therapists expected less therapeutic success for Syrian patients compared to Ukrainian patients. Gender did not influence the results.Conclusions: The study shows that refugee background and country of origin influence psychotherapists’ readiness to treat PTSD and their expectations of treatment success. These findings highlight potential reasons for the undertreatment of refugees and suggest opportunities for intervention and training, such as informing therapists about effective treatments for refugee patients.